2009
DOI: 10.1590/s0102-67202009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da suplementação dietética de arginina na cicatrização das anastomoses colônicas em ratos

Abstract: InTRODUÇÃOCicatrização adequada é considerada fundamental para o sucesso de qualquer intervenção cirúrgica, e uma falha neste processo pode levar à deiscências das suturas e graves consequências. A medida em que o processo fisiológico da cicatrização tornou-se progressivamente compreendido, fatores que influenciam este processo foram sendo descobertos e avaliados.Falhas nas anastomoses intestinais resultam em deiscências e fístulas, associadas a alta morbi-mortalidade. Já foram bem identificadas causas locais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Many studies have shown clear benefit of the use of immune- modulating enteral formulas by various mechanisms, because they enhancing the immune status in its various aspects 11 . However, the use of individual components present in these formulas did not bring such positive evidences and literature is divergent as regards to its results 4 , 5 . The omega-3 polyunsaturated fatty acids have been shown to play an important role in the mechanisms involving cellular signaling pathways that culminate with an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many studies have shown clear benefit of the use of immune- modulating enteral formulas by various mechanisms, because they enhancing the immune status in its various aspects 11 . However, the use of individual components present in these formulas did not bring such positive evidences and literature is divergent as regards to its results 4 , 5 . The omega-3 polyunsaturated fatty acids have been shown to play an important role in the mechanisms involving cellular signaling pathways that culminate with an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 96%
“…However, due to the complex mechanism of interaction between absorption processes, membranes attachment and intracellular signaling, it is known that formulas consisting of amino acids, essential fatty acids, trace elements, vitamins, nucleotides and nucleosides, were effective when using together, while the use of specific nutrients alone was associated with less clear benefits and with divergent results 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering these findings, the present study aimed to compare the healing processes in the abdominal wall of rats, according to biochemical and histopathological parameters, after treatment with arginine+PBS solution (arginine group) or PBS solution (control group), both injected intraperitoneally. Experimental studies in rats were performed to verify the effects of arginine on postoperative healing of intestines and skin, burns, incorporation of synthetic material in the abdominal wall, with different doses and routes of administration, such as oral, subcutaneous and intraperitoneal[16][17][18][19][20] .…”
mentioning
confidence: 99%